Menentukan Kematangan Buah Manggis Menggunakan Metode Summary Squared Error (SSE) yang Diaplikasikan pada Belt Conveyor Pemisah Buah - Hari Risanti Saputra; Firdaus - -; Derisma - - (Jurnal Ilmiah Poli Rekayasa, 2014)
All parts of mangosteen are useable. In order to obtain some qulified mangosteen, it is need to make a belt conveyor sorting system which is able to sort based on it’s diameter and maturity.   To obtain the maturity decision it is used Sum Squared Error (SSE) methode which find the minimum error of image RGB value between mangoosten rind color and the color  templates. When need to derive the diameter, it is utilize the hough circle transform method.The results give 86% accuracy of maturity detection, 10.9% error accuracy of diameter measurements when mangosteen  stalks  are up and  3.4% error in diameter value when  mangoosteen stalks are down .